2009
DOI: 10.1007/s11910-009-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

Cell-based therapies in Parkinson’s disease

Abstract: The possibility of using stem cells to treat Parkinson's disease has excited physicians and patients alike. However, after many encouraging open-label studies of fetal cell transplantation for Parkinson's disease, three randomized, double-blind, placebo-controlled studies found no net benefit. In addition, patients in two of the studies developed dyskinesias that persisted despite reductions in medication. To realize the promise of stem cells, research has been undertaken to understand and overcome the dual pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Potential sources for cell replacement have included fetal ventral mesencephalon tissue and various stem cell types that can differentiate into dopaminergic neurons. Numerous experimental replacement therapies have been examined in preclinical animal models and in clinical trials (reviewed in [95,96]). MSCs have also been examined in animal models of PD, for their neurorestorative effects and as delivery vehicles for production of additional factors.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Potential sources for cell replacement have included fetal ventral mesencephalon tissue and various stem cell types that can differentiate into dopaminergic neurons. Numerous experimental replacement therapies have been examined in preclinical animal models and in clinical trials (reviewed in [95,96]). MSCs have also been examined in animal models of PD, for their neurorestorative effects and as delivery vehicles for production of additional factors.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…After many encouraging open-label studies of fetal cell transplantation for PD, three randomized, double-blind, placebo-controlled studies found no net benefit. In addition, patients in two of the studies developed dyskinesias that persisted despite reductions in medication (87). Interestingly, recent reports have shown that as early as 14 years after transplantation into the striatum of individuals with PD, grafted nigral neurons are found to have Lewy body-like inclusions that stained positively for α -synuclein and ubiquitin and to have reduced immunostaining for DA transporter (112, 126).…”
Section: Npc Transplants and Brain Repairmentioning
confidence: 99%
“…Although these clinical trials clearly indicate room for improvement to enhance graft function as well as reduce unwarranted dyskinetic side effects, they also indicate positive short‐term clinical benefit in a subset of patients similar to open‐label trials and highlight potential problems to tackle, understand, and eventually resolve in future studies (reviews150–154). Specifically, a consensus must come to a standardization for method of dissection, age and number of donor fetuses, length of tissue incubation postisolation, as well as the target site, number of sites to graft, and a variety of other surgical parameters with clinical relevance reviewed elsewhere 45,155.…”
Section: Neuronal Transplantation In Parkinson's Diseasementioning
confidence: 99%